Abnormal Oscillatory Neural Coupling in Children with Language-Learning Problems and Auditory Processing Disorder. - Gilley, Phillip M.; Walker, Nicholas K.; Sharma, Anu (Seminars in Hearing, 2014)
Children with language-learning problems (LLP) often demonstrate auditory processing deficits on tasks using nonlinguistic stimuli, which may indicate an underlying auditory processing disorder (APD) that leads to delayed language skills. However, recent studies of event-related potentials provide evidence that APD is the result of, rather than the cause of, language impairments in children with LLP. To further address these conflicting accounts, we examined event-related spectral perturbations (ERSPs) in 14 children with LLP and in 14 age-matched, normal hearing controls. ERSPs were computed from electroencephalogram (EEG) responses to nonlinguistic speech sounds in two different stimulus rate conditions. Results revealed that children with LLP have abnormal shifts in the characteristic operating frequencies (COFs) and phase-amplitude coupling of the alpha and beta EEG bands. Further, children with LLP show multiple COFs in the beta EEG band, which are not present in normal-hearing controls. These results suggest that insufficient oscillatory neural coupling may underlie the APD and language deficits present in children with LLP and might further be explained by interhemispheric asymmetries in this population.